Case report: A case of severe retropharyngeal edema after COVID-19 successfully treated with intravenous immunoglobulin - Suzuki, Takanori; Kono, Toya; Satoshi, Hisada; Uchida, Hidetoshi; Ota, Seiichiro; Tateya, Ichiro; Yoshikawa, Tetsushi (Frontiers in Pediatrics, 2023)
Multisystem inflammatory syndrome in children (MIS-C) has been widely reported, mainly in Western countries. The clinical features of MIS-C and Kawasaki disease are similar. The latter is common in Asian countries, including Japan. Meanwhile, the incidence of MIS-C seems to be low in Japan. Retropharyngeal edema is relatively common in older patients with Kawasaki disease and has been reported in a few patients with MIS-C. We describe a case of severe retropharyngeal edema after coronavirus disease 2019 (COVID-19) that improved quickly with high-dose of intravenous immunoglobulin treatment. Onset of retropharyngeal edema was 3 weeks after COVID-19. The patient received appropriate intravenous antibiotics for 5 days, but his symptoms worsened. Therefore, we suspected that his retropharyngeal edema was caused by suspected MIS-C even though he did not have the typical clinical symptoms of suspected MIS-C such as gastrointestinal symptoms and shock. Retropharyngeal edema was refractory to antibiotic therapy but lessened quickly with high-dose immunoglobulin therapy, without other typical clinical manifestations of MIS-C, suggesting that early immunoglobulin therapy might prevent the progression of MIS-C.